The testament [compact disc] - Grisham, John (Random House Audio, 1999)
Troy Phelan is a self-made billionaire who is eccentric, reclusive, and looking for a way to die. His heirs are circling like vultures. Nate O'Riley is a high-octane Washington litigator just emerging from his fourth stay in rehab armed with his fragile sobriety, good intentions, and resilient sense of humor. Rachel Lane is a young woman who walked away from the modern world to live and work with a primitive tribe of Indians in the jungles of Brazil. This story mixes legal suspense with adventure.